Análise do risco de câncer de mama por meio de APP versus comparação com a mamografia - Macêdo, Cinira Maiara Matos Holanda (2023)
Breast cancer was shown to be the most prevalent in the world in 2020; with 685 thousand deaths related to this disease, it is the main cause of death from cancer in the female population, with an increasing trend. The main causes of breast cancer are related to endocrine, behavioral and genetic factors. The use of applications for mobile devices can be of relevant importance in promoting health, helping to identify women who need medical investigation. The objective of the present study was to validate the capacity of an application developed at GEEON, an extension of the Department of Surgery at the Federal University of Ceará, to identify patients with a suspicious profile for breast cancer through comparison with a mammography exam. This is a quantitative, prospective and cross-sectional study carried out from 2021 to 2022. Initially, interviews were carried out with the patients using the research instrument, with questions addressed: breast complaints, obstetric history, menstrual cycles, breastfeeding, education, income, family history of cancer, breast characteristics, dietary practices and history of imaging or pathological examinations used to diagnose BC. Then, the analysis of these data was compared with the BIRADS from the patients' mammography exam. After univariate and multivariate analysis, the most statistically significant risk and protective factors were identified in the application to identify women who need medical evaluation and risk investigation for breast cancer, and found: BMI; breastfeeding for more than 6 months; breast lump; diet of red meat, sausages and canned foods; period since the last mammogram and previous biopsy. The present study validated the ability of the mobile application to identify patients at risk for breast cancer, with an accuracy of more than 79% between the application's findings and the BIRADS mammography.